No relationship between the nordic hamstring and two different isometric strength tests to assess hamstring muscle strength in professional soccer players - Moreno-Pérez, V.; Mendez-Villanueva, A.; Soler, A.; Del Coso, J.; Courel-Ibanez, J. (Physical Therapy in Sport, 2020)
There was a poor association among the mechanical outputs of the eccentric and isometric tests. Isometric and eccentric exercises identified hamstring weakness or asymmetry differently. Each test must be used for particular purposes during the hamstring injury rehabilitation. Objectives: To investigate the relationship between one eccentric and two isometric tests commonly used to assess hamstring strength in professional soccer.